Analysis of The Integrated Farming Income in The SMD (Sarjana Membangun Desa) Program In Padang City (Case Study: Tani Ternak Sepakat Group) - Amelira Haris Nasution; Nofialdi Nofialdi; Ferdhinal Asful (Indonesian Journal of Agricultural Research)
The purpose of this research is to analyze the farming income of farmers who develop integrated farming system after and before getting the SMD Program in Padang City by involving Tani Ternak Sepakat Group as case study. This research was  designed as a  case study conducted from June 2012 to July 2012 in Kurao Pagang, Padang City, West Sumatera. In this research, the researcher used descriptive qualitative and descriptive quantitative design.